Expression of Potential Regulatory Genes in Abdominal Adipose Tissue of Broiler Chickens during Early Development. (16th January 2014) - Bohannon-Stewart, Ann; Kelley, Gary; Kimathi, Boniface; Subramanya, Sri Harsha K. V.; Donkor, Joseph; Darris, Carl; Tyus, James; Payne, Ashley; Byers, Shannon; Hui, Dafeng; Nahashon, Samuel; Chen, Fur-Chi; et al.
Abstract : The identities of genes that underlie population variation in adipose tissue development in farm animals are poorly understood. Previous studies in our laboratory have suggested that increased fat tissue involves the expression modulation of an array of genes in broiler chickens. Of special interest are eight genes, FGFR3, EPHB2, IGFBP2, GREM1, TNC, COL3A1, ACBD7, and SCD . To understand their expression regulation and response to dietary manipulation, we investigated their mRNA levels after dietary manipulation during early development. Chickens were fed either a recommended standard or a high caloric diet from hatch to eight weeks of age (WOA). The high caloric diet markedly affected bodyweight of the broiler birds. mRNA levels of the eight genes in the abdominal adipose tissue were assayed at 2, 4, 6, and 8 WOA using RT-qPCR. Results indicate that (1) FGFR3 mRNA level was affected significantly by diet, age, and diet:age interaction; (2) COL3A mRNA level was repressed by high caloric diet; (3) mRNA levels of EPHB2, ACBD7, and SCD were affected by age; (4) mRNA level of TNC was modulated by age:diet interaction; (5) changes in GREM1 and IGFBP2 mRNA levels were not statistically different.